Measurements of the diffusion coefficients of CFC-11 and CFC-12 in pure water and seawater - Zheng, Min; De Bruyn, Warren J; Saltzman, Eric S (Journal of Geophysical Research: Oceans, 1998)
Trichlorofluoromethane (CCl3F; CFC-11) and dichlorodifluoromethane (CCl2F2; CFC-12) have been widely used as tracers of oceanic circulation and mixing on decadal timescales. In order to estimate their transfer rate across the air-sea interface, liquid-phase diffusion coefficients are needed In this study the diffusivities of CFC-11 and CFC-12 in pure water were measured over the temperature range 0.6–30°C. Diffusivities of CFC-11 in pure water ranged from (5.24±0.25)×10−6 cm2S−1 at 0.6°C to (1.13±0.05)×10−5 cm2S−1 at 30.3°C and a fit to the data yielded the equation D CFC-11 = 0.015 exp (−18.1/RT), where R is the universal gas constant in kJ mol−1 K−1 and T is the temperature in Kelvin. Diffusivities of CFC-12 in pure water ranged from (5.38±0.22)×10−6 cm2 s−1 at 0.6°C to (1.26±0.05)×10−5 cm2 s−1at 30.3°C and the temperature dependence can be expressed as DCFC-12= 0.036 exp (−20.1/RT). The estimated uncertainty in both equations is <3%. Experiments were also carried out in seawater for each compound. For CFC-11 the diffusivity in seawater was not significantly different from that in pure water. However, the diffusivity of CFC-12 in seawater was found to be 7.2±3.0% lower than that in pure water. Schmidt numbers for both CFC-11 and CFC-12 in pure water and seawater were estimated from the data.